A randomised controlled feasibility trial of alcohol consumption and the ability to appropriately use a firearm. Issue 6 (3rd December 2009) - Carr, B G; Wiebe, D J; Richmond, T S; Cheney, R; Branas, C C
Abstract : Objective: To show the feasibility of using a controlled trial to investigate the effect of alcohol on firearm use. Methods: Randomised, blinded, placebo-controlled trial in the Firearm Usage and Safety Experiments (FUSE) Lab. Treatment subjects (male, 21–40-year-old, non-habitual drinkers, with no professional firearms training) received alcohol; control subjects received placebo alcohol. The AIS PRISim Firearm Simulator, including real pistols retrofitted to discharge compressed air cartridges that simulate firearm recoil and sound, was used to measure firearm performance. Accuracy and speed for target shooting, reaction time scenarios, and scenarios requiring judgement about when to use a gun were measured. Results: 12 subjects enrolled in the trial, completing 160 training scenarios. All subjects in the alcohol arm reached target alcohol level. 33% of placebo subjects reported alcohol consumption. Mechanical malfunction of the simulator occurred in 9 of 160 (5.6%) scenarios. Intoxicated subjects were less accurate, slower to fire in reaction time scenarios, and quicker to fire in scenarios requiring judgement relative to controls. Conclusions: The feasibility of a randomised, controlled trial exploring the relationship between alcohol consumption and firearm use was shown. The hypothesis that alcohol consumption worsens accuracy and retards judgement about when to use a gun should be tested. Larger trials could inform policies regarding firearm use while intoxicated.